2006
DOI: 10.1128/iai.01822-05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ConcomitantSchistosoma haematobiumInfection on the Serum Cytokine Levels Elicited by AcutePlasmodium falciparumMalaria Infection in Malian Children

Abstract: Polyparasitism is common in the developing world, and interactions that alter disease severity may occur. We previously demonstrated that infection with Schistosoma hematobium was associated with protection against Plasmodium falciparum infection in children who were 4 to 8 years old. In this study, we determined whether underlying helminth infections affected the cytokine responses to acute falciparum malaria. A total of 338 schistosomiasis-positive [Sch(؉)] children who were 4 to 14 years old were matched by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 34 publications
2
68
1
Order By: Relevance
“…23 A study on children conducted in Mali in 2002-2003 presented both epidemiological and biological approaches and concluded on a protective effect of infection with urinary schistosomiasis on malaria. 8,9 In contrast, other studies suggested an additive or synergistic effect of coinfection.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…23 A study on children conducted in Mali in 2002-2003 presented both epidemiological and biological approaches and concluded on a protective effect of infection with urinary schistosomiasis on malaria. 8,9 In contrast, other studies suggested an additive or synergistic effect of coinfection.…”
Section: Discussionmentioning
confidence: 59%
“…[4][5][6]17 In this study, we focused on the interaction between schistosomiasis and malaria infection. Several biological studies have shown a synergistic effect of coinfection, 16,[18][19][20][21] whereas other studies suggested an acceleration or regulation toward protective profile of the acquired immunity against malaria in children coinfected with malaria and schistosomiasis 9,22 and another study did not find an association. 23 A study on children conducted in Mali in 2002-2003 presented both epidemiological and biological approaches and concluded on a protective effect of infection with urinary schistosomiasis on malaria.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This has led to suggestions that interspecific interactions are of little importance in shaping pathogen communities under natural conditions [6][7][8][9][10][11][12][13][14][15][16]. This debate continues despite the fact that the importance of pathogen interactions is becoming increasingly obvious in clinical settings [17][18][19][20][21]. One possible explanation for the apparent lack of interactions between pathogen species in wild host systems is that the pathogens may be temporally asynchronous within their hosts, resulting in a form of niche segregation and reducing the likelihood of direct interaction [12,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies that have assessed this question have yielded conflicting results indicating that larger and better designed studies are needed. [17][18][19][20] To date, studies assessing the coinfection of helminths and malaria have mainly focused on the asexual forms of P. falciparum (reviewed in reference 21). However, there are indications that helminth infections may also influence the prevalence or density of P. falciparum gametocytes, the parasite stage responsible for transmission of infections to mosquitoes.…”
Section: Introductionmentioning
confidence: 99%